2021
DOI: 10.1097/jom.0000000000002377
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Work-Life Balance and Productivity Before and During Work From Home

Abstract: Objectives: Considering the prevailing work from home (WFH) arrangement globally due to COVID-19, this paper aims to compare job-related and psychosocial factors before and during WFH setup; and to determine the relationship of these factors to work-life balance (WLB) and productivity. Methods: A total 503 employees from 46 institutions answered the online questionnaire, 318 of whom met the inclusion criteria. Paired t test and structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 47 publications
2
32
0
1
Order By: Relevance
“…Currently, there are little data regarding patterns of sleep and work productivity during the COVID-19 pandemic in this population. Recent reports suggest that working remotely may be associated with worse productivity, which itself is related to mental health and sleep problems [ 39 , 40 , 41 ]. However, our data indicate that sleep quality and work productivity were not directly related to each other and were influenced by different determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are little data regarding patterns of sleep and work productivity during the COVID-19 pandemic in this population. Recent reports suggest that working remotely may be associated with worse productivity, which itself is related to mental health and sleep problems [ 39 , 40 , 41 ]. However, our data indicate that sleep quality and work productivity were not directly related to each other and were influenced by different determinants.…”
Section: Discussionmentioning
confidence: 99%
“…We included the question about work location as a response to the COVID-19 pandemic, which was not part of the original study protocol. The consequences of work-from-home on workers’ productivity and well-being have gained increasing attention in research since the start of the COVID-19 pandemic (Tejero et al 2021 ). Our results showed no significant influence of the work location on work–life interference.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed no significant influence of the work location on work–life interference. However, a recent study among office workers has shown that during work-from-home, the social support of colleagues declined, leading to increased stress, resulting in lower productivity and a poorer work–life balance (Tejero et al 2021 ). Our study population covered a wide range of occupations and seniority levels among office workers in academia.…”
Section: Discussionmentioning
confidence: 99%
“…Working from home causes difficulties in attaining psychological detachment because of the absence of physical distinction between work and home. Commuting to work used to act as a natural boundary between work and home and has vanished in the work-from-home format (Tejero et al, 2021).…”
Section: The Problemmentioning
confidence: 99%
“…A decrease in psychological detachment causes an increase in stress. Psychological detachment (PD) is an important predictor of wellbeing (Tejero et al, 2021). Psychological detachment is part of the recovery experiences, and the recovery process constitutes the reverse of the strain process (Sonnentag & Fritz, 2007).…”
Section: Importance Of the Problemmentioning
confidence: 99%